GIS-based multicriteria analysis for landslide monitoring base station evaluation using ordered weight averaging - Mustafa I.S. (Alpha Publishers, 2023)
A slope monitoring system is important for power utilities since its assets, especially transmission lines at high altitude areas, are vulnerable to landslide. One of the best real-time monitoring approaches is to install appropriate sensors for detecting slope failure.Sensor data is collected electronically via antenna and sent to a centralized data location via communication channels. This telemetry system relies on wide area communication accessible at that location. To improve network performance, the position of every base stations should be strategically planned to ensure data integrity. However, there are numerous factors to be considered when choosing the alternative of the communication technologies such as topography, accessibility, power supply availability and others. Therefore, this study proposes a Geographical Information System (GIS)-based system with an emphasis on the multi-criteria decision analysis (MCDA) for preliminary site suitability of base station placement. The factors are classified into five main criteria which are technical, topography, risk assessment, land cover and accessibility criteria and then the weight is justified by the experts for final weight consensus. Fuzzy membership function is used in standardization stage to reclassify and transform the input criteria data based on a range of specific set. The Analytical Hierarchy Process (AHP) is used to generate an alternative decision using a multi-criteria evaluation (MCE) technique. The criteria maps were combined and overlaid using weighted linear combination (WLC) techniques and ordered weighted average (OWA). The results yielded that GIS-WLC and OWA model can be integrated into MCDA to select and the optimal site of antenna base station placement. 2020 Alpha Publishers. All rights reserved.